Hate speech dynamics against African descent, Roma and LGBTQ+ communities in Portugal - Carvalho, P.; Matos, B.; Santos, R.; Batista, F.; Ribeiro, R. (Proceedings of the 13th Conference on Language Resources and Evaluation (LREC 2022), 2022)
This paper introduces FIGHT, a dataset containing 63,450 tweets, posted before and after the official declaration of Covid-19 as a pandemic by online users in Portugal. This resource aims at contributing to the analysis of online hate speech targeting the most representative minorities in Portugal, namely the African descent and the Roma communities, and the LGBTQ+ community, the most commonly reported target of hate speech in social media at the European context. We present the methods for collecting the data, and provide insightful statistics on the distribution of tweets included in FIGHT, considering both the temporal and spatial dimensions. We also analyze the availability over time of tweets targeting the aforementioned communities, distinguishing public, private, and deleted tweets. We believe this study will contribute to better understand the dynamics of online hate speech in Portugal, particularly in adverse contexts, such as a pandemic outbreak, allowing the development of more informed and accurate hate speech resources for Portuguese.